Blue Economy and Sustainable Marine Tourism: An Islamic Economic Perspective on Tiga Pier Beach, Pamekasan - Moh. Lutfi; Fahrurrozi; Zakiatur Riskiyah (Kartika: Jurnal Studi Keislaman, 2025)
Tiga Pier Beach in Pamekasan Regency has emerged as a marine tourism destination contributing to local socio-economic development. Prior to tourism initiatives, the area lacked adequate waste management; however, the introduction of daily cleaning services has reduced environmental degradation. This study explores the application of blue economy principles creativity, innovation, local resource utilization, and zero-waste practices in fostering sustainable marine tourism, analyzed through an Islamic economic lens. Using a descriptive qualitative method, data were obtained from Badan Usaha Milik Desa (BUMDes) and Civil Service officials in Branta Village. Findings reveal that blue economy implementation is reflected in four key practices: (1) natural efficiency through low CO₂ emissions and resource conservation, (2) zero-waste management, (3) community empowerment to enhance social awareness, and (4) income diversification for coastal residents. These strategies have improved both economic benefits and the quality of tourist destinations. The study concludes that integrating blue economy principles with Islamic economic values can strengthen sustainability outcomes, providing a viable model for marine tourism development in Muslim-majority coastal regions.